2009
DOI: 10.1080/07036330903145906
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Order Elections versus First‐Order Thinking: How Voters Perceive the Representation Process in a Multi‐Layered System of Governance

Abstract: Second-order election models are based on several assumptions about individual-level motivations. These can be summarized by a transfer hypothesis: individuals presumably apply their evaluations of national-level phenomena to the EU level when voting in EU elections. In contrast, a suis generis hypothesis stipulates that voters evaluate the EU on its own performance terms. This paper tests these competing hypotheses. We find considerable support for both models. In the election context, where national institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 19 publications
4
54
1
Order By: Relevance
“…only marginally better at subnational level, reflecting perhaps the issue of differentiated voting in second-order elections (Clark & Rohrschneider, 2009), although we found no strong evidence in the literature between second-order elections and improved gender outcomes.…”
Section: Theoretical Backgroundcontrasting
confidence: 53%
See 1 more Smart Citation
“…only marginally better at subnational level, reflecting perhaps the issue of differentiated voting in second-order elections (Clark & Rohrschneider, 2009), although we found no strong evidence in the literature between second-order elections and improved gender outcomes.…”
Section: Theoretical Backgroundcontrasting
confidence: 53%
“…more positive institutional culture and discourse instigated by the new institutions in Wales-as well as in Scotland- (Stirbu, 2011), and, more generally, the differentiated voting effect between national and subnational levels (Clark & Rohrschneider, 2009). However, in the Welsh case, explanations regarding the effect of the electoral system on gender representation may seem counterintuitive.…”
Section: Opening the 'Gates' Of Electoral Opportunity Structure For Wmentioning
confidence: 99%
“…Yet, recent scholarship has shown that EUspecific motivations matter to vote choices in EP elections (Hobolt et al 2009;De Vries et al 2011;Hobolt and Wittrock 2011;Hobolt and Spoon 2012). For example, Hobolt et al (2009) 6 have demonstrated that voters are more likely to defect from a governing party if they have more Eurosceptic preferences than the party (see also Clark and Rohrschneider 2009 Hobolt and Spoon 2012). In a systematic comparison of the "second-order" and the "Europe matters" theses, Hix and Marsh (2007), using aggregate-level data from six EP elections, show that large parties tend to lose votes in EP elections regardless of their position on European integration.…”
Section: The Crisis and The Eurosceptic Votementioning
confidence: 99%
“…Scholars have traditionally conceived of EP elections as second-order national elections where vote choices are primarily based on domestic political considerations (Reif and Schmitt 1980;van der Eijk and Franklin 1996). However, recent evidence suggests that concerns about European integration and the euro do affect vote choices (Clark and Rohrschneider 2009;Hobolt et al 2009;De Vries et al 2011;Hobolt and Spoon 2012;Tillman 2012). The growing involvement of EU institutions in national economic policy during the crisis has further eroded citizens' perceptions that their own government is responsible for economic outcomes, and blame has partly been shifted to the EU (Hobolt and Tilley 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have sought to differentiate between different types of second order elections, moving beyond European Parliamentary (EP) ballots to understand the behavior and engagement of voters at local, regional or state level (see, for example, Franklin and Weber, 2010;Marsh and Mikhaylov, 2010). In doing so, research conducted about second order elections often relates to how citizens perceive and participate in them (see, for example, Carrubba and Timpone, 2005;Schmitt, 2005;Clark and Rohrschneider, 2009), rather than about how the media report different types of election campaigns.…”
Section: A U T H O R C O P Ymentioning
confidence: 99%